Airway foreign bodies in infants younger than 6 months: a referral center experience - Mohammad Ashkan Moslehi (Hygeia Press di Corridori Marinella, 2022)
Background: Although the most common age for foreign body (FB) aspiration (FBA) is considered from 1 to 4 years old, it can even happen earlier.  Aim: The purpose of this study is to evaluate the occurrence of FBA in 6-month infants and younger. Material and methods: This study is a retrospective analysis of all the cases of FBA in infants under 6 months admitted to Namazi Hospital in Shiraz, Iran, and who underwent flexible fiberoptic bronchoscopy from September 2017 to March 2019.  Results: Medical records of 38 infants under 6 months of age who underwent flexible fiberoptic bronchoscopy with a diagnosis of FBA were reviewed retrospectively. 71.1% of the infants were male. History regarding prematurity was positive in 63.2% of the neonates. 55.3% had different degrees of tooth eruption. Sudden-onset cough (97.4%), noisy breathing (92.1%), and cyanotic spells (52.6%) were the 3 most common reported symptoms before hospitalization. Most (73.7%) aspirations occurred in the presence of parents or caregivers. 7.9% of the infants had normal radiographic results. Only 21.1% of the patients were diagnosed and managed within 24 hours after the aspiration. The most common aspirated FBs were organic objects.  Conclusion: Although FBA is more common in older children, it can also occur in infants younger than 6 months. Families, and especially physicians, should be fully informed of the possibility of aspiration at an early age, which can reduce the occurrence of FBA and its irreversible effects.